2003
DOI: 10.1046/j.1440-1746.2003.02973.x
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling in hepatocellular carcinoma: Analysis of mutation and expression of beta‐catenin, T‐cell factor‐4 and glycogen synthase kinase 3‐beta genes

Abstract: Our present findings strongly suggest that mutations of beta-catenin, as well as overexpression of beta-catenin and the Tcf-4 gene, independently activate the Wnt pathway in HCC, with the target gene most likely to be C-myc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 23 publications
7
83
0
1
Order By: Relevance
“…However, mutations of β-catenin and/or APC genes are detected only in 20-30%, whereas axin1 mutations are rare in HCC [18,[33][34][35][36][37][38]. Previous reports suggest that several signaling components upstream of β-catenin may be involved for wild-type β-catenin accumulation to occur in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, mutations of β-catenin and/or APC genes are detected only in 20-30%, whereas axin1 mutations are rare in HCC [18,[33][34][35][36][37][38]. Previous reports suggest that several signaling components upstream of β-catenin may be involved for wild-type β-catenin accumulation to occur in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14]34,35,39,[46][47][48][49] Dysregulation of this pathway can be caused by mutations in any components (CTNNB1, AXIN or FZD7) in colon cancers, HCCs and other cancers. 46,49,50 Suzuki et al 36,42 demonstrated recently that epigenetic loss of SFRP gene family functions may contribute to the progression of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although these two genes are frequently up-regulated in HCC, a direct link between activation of the ␤-catenin pathway and the genes' overexpression in the liver is controversial (24)(25)(26)(27). Cyclin D1 mRNA was induced in adult Apc Ϫ/Ϫ livers on D7 and in both Apc Ϫ/Ϫ and PK͞c-Myc liver tumors (Fig.…”
Section: Liver-targeted Apc Ablation Activates ␤-Catenin Signaling Andmentioning
confidence: 99%